Satisfaction towards domiciliary care services and the unmet needs among stroke patients in Kota Bharu District - Emeran, Nurul Ain Mohd (2018)
Domiciliary care is a multidisciplinary rehabilitation care which provides the continuity of care at the community setting. It requires the involvement of caregivers in providing continuous care at home with guidance by the health professionals. This study examined the factors associated with caregivers’ satisfaction towards provided domiciliary care services and the unmet needs for care among patients who are not eligible to receive domiciliary care in Kota Bharu district as perceived by the caregiver. This study was divided into three parts, the retrospective record review of stroke patients from HRPZ II and Hospital USM, a caregiver satisfaction survey for patients who received domiciliary care, and an unmet needs survey as perceived by the caregiver of stroke patients who were not eligible to receive domiciliary care services. Caregiver satisfaction was measured using the validated FAMCARE questionnaire. The unmet need was measured using the UN CARE questionnaire. Multiple linear regression was used to identify the determinants of satisfaction and the unmet needs. Seventy nine (23.9%) of the randomly selected 330 stroke patients received domiciliary care services, whereas others received either nursing care visit 121 (36.7%) or outpatient service 130 (39%). Out of those 219 (66.4%) who were referred to be assessed for eligibility to receive domiciliary care services, only 79 (36.1%) fulfil the eligibility criteria. Most eligibility criteria were fulfilled by most of the patients except availability of caregiver during therapy visit. Caregiver’s satisfaction in general, towards provided domiciliary care services was found to have association with the family conference prior to discharge (adjusted b= 0.51, 95%CI 0.31,0.69, p<0.001). Satisfaction in term of information giving and physical care were associated with only family conference prior to discharge. Besides family conference prior to discharge, satisfaction subscale on psychosocial care was also determined by duration of illness. Satisfaction in term of availability of care was also associated with care giver income and strain index. The unmet needs in general, among non-recipient of domiciliary care services was found to be associated with age of caregivers (adjusted b= -0.002, 95%CI -0.004,-5.34×10-5, p = 0.044), caregivers with own income (adjusted b= 0.11, 95%CI 0.03,0.19, p = 0.008), high caregiver’s burden (adjusted b= -0.13, 95%CI -0.18,-0.07, p<0.001), and family conference prior to discharge (adjusted b= - 0.19, 95%CI -0.25,-0.14, p<0.001). Unmet needs on support was associated with impairments, activity limitations, and patient-caregiver who stayed together. Unmet needs on engagement of care was associated with age of caregivers, caregivers with own income, high caregiver’s burden, and family conference prior to discharge. Unmet needs on benefit of care was associated with activity limitations, high caregiver’s burden, and family conference prior to discharge. The study found that the domiciliary care services in Kota Bharu generally met the purpose to those who received. The family conferences were important for those who were not eligible to receive the services.